Evaluation of COVID-19 vaccine effectiveness : interim guidance, 17 March 2021 (World Health Organization, 2021)
Vaccine effectiveness and impact document provides interim best practice guidance on how to assess COVID-19 vaccine effectiveness (VE) using observational study designs. It discusses critical considerations in the design, analysis and interpretation of COVID-19 VE evaluations, as biased results may be produced even in settings where data completeness and quality are high. This guidance is targeted mostly for evaluations undertaken in low- and middle-income countries but most of the concepts apply to VE evaluations in high-income settings as well.
Keywords: Betacoronavirus; veřejné zdravotnictví; epidemický výskyt choroby; infekční lékařství; Disease Outbreaks; heterologní imunita; vakcíny; preventivní medicína; COVID-19 Vaccines; Immunity, Heterologous; vakcíny proti COVID-19; COVID-19; Vaccines